Farm Buildings as Drivers of the Rural Environment - Picuno, Pietro (Frontiers in Built Environment, 2022)
Farm buildings play a central role on the sustainability of the rural environment. Conceived to host biological productions, the farm building constitutes indeed an unparalleled example in the wide epistemological construction sector. Due to its peculiar interactions with indoor and outdoor built environment, it raises architectural and technical issues different from other buildings. The role that these buildings have historically played is strictly connected with the surrounding context, due to the need of the farmer to live in close contact with agricultural land and animal husbandry. Human activities have then decisively influenced the rural environment, as well as the visual perception of its landscape. The increasing sensitivity about the concept of sustainable development of the built environment is currently stimulating the valorisation of farm buildings. In the present review paper, a general literature analysis about the peculiarity of farm buildings and their internal and external environmental conditions is presented. Several cases of survey, reuse and valorisation of farm buildings in the World are reported as well, with special attention to Southern Italy, whose results would be extrapolated or generalized to other regions. A focus is also reported on the wider opportunities enabled by the implementation of new technologies for the survey, analysis and planning of the interactions between farm buildings and rural environment. Main conclusions are that farm buildings play a driving role for the rural environment, thanks to the ecological function they perform, as well as to their socio-economic and cultural heritage, at the base of the rural development.